Actual problems of co-investment market - Ermolaeva, Marina (My University, 2014)
Certain reform-based transformations and positive practical improvements can be seen in Ukraine’s economy currently.
Keywords: іноземні інвестиції; інвестиційний клімат; ринок; foreign investment; investment climate; market; иностранные инвестиции; инвестиционный климат; рынок